Motivation and Interest in Traveling of Young Traveler During Revenge Tourism - Then, Julita; Yulius, Kevin Gustian (Stupa, 2022)
Revenge tourism is a travel trip that is meant to take revenge after the end of the pandemic period and is carried out for those who have previously canceled their tour due to the pandemic. Young travelers are one of the fastest growing and most dynamic markets of the tourism sector in this study, their motivation and interest in traveling are influenced by several factors. The study uses a descriptive quantitative approach with the aim of looking at the motivations of young travelers in traveling after the pandemic ends. With the purposive sampling method, it was found that the motivations that influence young travelers' interest in traveling during revenge tourism are escape motivation, relaxation, strengthening family bonds, self-fulfillment, romance, wish fulfillment, financial security, and leisure time. While the motivation that has no effect is the motivation to play, prestige, social interaction, and educational opportunity.